2005
DOI: 10.1111/j.1365-2222.2005.02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of intermittent and persistent allergic rhinitis: DREAMS study group

Abstract: SummaryBackground In the Allergic Rhinitis and its Impact on Asthma (ARIA) classification, intermittent and persistent rhinitis were proposed to replace seasonal and perennial allergic rhinitis (AR). Aim To better understand the ARIA classification of rhinitis. Methods A cross-sectional study was carried out in 591 patients consulting ENT or allergy specialists for AR and 502 control subjects. The diagnosis of AR was based on a score for allergic rhinitis (SFAR) X7. Patients were classified according to the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
156
4
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(199 citation statements)
references
References 31 publications
20
156
4
14
Order By: Relevance
“…• the majority of patients are sensitized to many different allergens and therefore exposed throughout the year (33,62,(67)(68)(69). In many patients, perennial symptoms are often present and patients experience seasonal exacerbations when exposed to pollens or molds.…”
Section: Intermittent (Iar) and Persistent Allergic Rhinitis (Per)mentioning
confidence: 99%
“…• the majority of patients are sensitized to many different allergens and therefore exposed throughout the year (33,62,(67)(68)(69). In many patients, perennial symptoms are often present and patients experience seasonal exacerbations when exposed to pollens or molds.…”
Section: Intermittent (Iar) and Persistent Allergic Rhinitis (Per)mentioning
confidence: 99%
“…PER is a distinct category of AR that merits special attention in the clinic, as patients with PER are at higher risk for sequelae including asthma 2, 28. Topical treatments are recommended for PER,2 in part to avoid the long‐term safety concerns associated with systemic medications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the SLIT natural allergen tablet modality (n = 7) studies or dose levels within a study) showed the lowest betweenstudy variability [tau 2 and I 2 (95% confidence intervals) for Hedges' g: 0.016 (58.5% (4.3-82%))], followed by SCIT with natural allergens (n = 7) with 0.039 [44.6% (0-76.7%)] and SLIT drops (n = 10) with 0.045 [51.9% (1.1-76.6%)]. The test was not applicable to SLIT with allergoid tablets and SCIT with allergoids, for which there were only one and two calculable studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This health problem affects as many as one in seven of the population in Western countries (2,3), with grass pollen as one of the major triggers (4).…”
Section: -434mentioning
confidence: 99%